An Analysis of Business Loans on the Payment of Micro, Small and Medium Enterprises (MSME) Loans - Hendra Utama (Jurnal Multidisiplin Sahombu, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in economic de-velopment by contributing to job creation and income generation. However, one of the major challenges faced by MSMEs is the ability to repay business loans. This study aims to analyze the factors influencing the repayment performance of MSME loans, focusing on business characteristics, loan terms, and external economic conditions. The research employs a quantitative approach using financial data from MSMEs that have received business loans from financial institutions. Multiple regression analysis is conducted to examine the relationship between loan repayment and factors such as loan amount, in-terest rate, business revenue, and duration of the loan. Additionally, the study explores the impact of external factors such as inflation and market conditions on MSME repay-ment behavior. The findings indicate that MSMEs with higher revenue and well-structured financial management exhibit better loan repayment performance. Conversely, high interest rates and economic instability negatively impact repayment capabilities. The study highlights the importance of flexible loan terms and financial literacy pro-grams to enhance MSME sustainability. This research provides valuable insights for poli-cymakers, financial institutions, and MSME owners in designing loan structures that im-prove repayment rates and financial stability. Future research is recommended to incor-porate qualitative aspects such as entrepreneurial mindset and business strategies to fur-ther understand MSME loan repayment behavior.